If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -2(2x + -7) = 2(x + -8) Reorder the terms: X + -2(-7 + 2x) = 2(x + -8) X + (-7 * -2 + 2x * -2) = 2(x + -8) X + (14 + -4x) = 2(x + -8) Reorder the terms: 14 + X + -4x = 2(x + -8) Reorder the terms: 14 + X + -4x = 2(-8 + x) 14 + X + -4x = (-8 * 2 + x * 2) 14 + X + -4x = (-16 + 2x) Solving 14 + X + -4x = -16 + 2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + X + -14 + -4x = -16 + -14 + 2x Reorder the terms: 14 + -14 + X + -4x = -16 + -14 + 2x Combine like terms: 14 + -14 = 0 0 + X + -4x = -16 + -14 + 2x X + -4x = -16 + -14 + 2x Combine like terms: -16 + -14 = -30 X + -4x = -30 + 2x Add '4x' to each side of the equation. X + -4x + 4x = -30 + 2x + 4x Combine like terms: -4x + 4x = 0 X + 0 = -30 + 2x + 4x X = -30 + 2x + 4x Combine like terms: 2x + 4x = 6x X = -30 + 6x Simplifying X = -30 + 6x
| 186x=1132-16 | | abs(3x+4)=-3 | | w-(-8)=47 | | -4.8=3.2 | | 25+10(12-x)=5(3x-7) | | 41x-12(x-4)= | | 20=20*log(x) | | 7x+17x-7=6(4x+10) | | x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 | | 0.5x+3=0.75-7.75 | | -5(6k+9)=-27+7k | | 20=20log(x) | | 0.4-0.107= | | 78=1/2h(5+8) | | 5.6x+3=4.6x | | 2x-(6x-4)=8-4x | | 10-7x=-(x-12) | | 16x=-50 | | 3y-20=40 | | 8k-2=4 | | Y^2+3y=x^3-x | | 3w-4=4w | | 18(x+3)=2(9x+2)+50 | | 5b-3=-9 | | 4n+15=4n+15 | | 8x+7(-3x-6)=-52-3x | | 10x+18=3(3x+4) | | -12+5x=3(x+2) | | 5-4=u | | 8x-4(40+x)=4 |